A DEA model to assess the educational system in Brazil. (21st March 2021) - Cardoso, Ingrid Gois; Lacerda, Daniel Pacheco; Piran, Fabio Sartori
This paper aims to measure and analyse the technical efficiency of municipal educational systems in cities in the state of Rio Grande do Sul, Brazil. The study used Data Envelopment Analysis (DEA) and output-oriented Variable Returns of Scale (VRS). The evaluation comprises variables that measure education quality, student flows, teacher training, school infrastructure and municipality expenses. The results evidenced that 50% of the sample is technically efficient, but that is possible to improve how the resources are applied even in this group of cities. Considering the inefficient cities, the model proved that the major part of cities has the potential to improve their results in all outputs: age-grade distortion rate, number of enrolled students, and results in exams of Portuguese and Math in the Prova Brasil. This study also demonstrated that efficiency in educational management cannot be associated only with expenditure and that, in some cases, there is the opportunity for reducing costs. Finally, the paper also presented the benchmarking for each inefficient city based in the number of enrolled students, which allow each city to identify the best practices between cities with similarities.